Correlation Between Diabetes Self-Management and Nutritional Status of Type 2 Diabetes Mellitus Patients in Hospital - Rizki Andriani; Yulia; Riri Maria (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
Diabetes Mellitus patients must maintain constant glucose control to avoid complications. Diet is one type of diabetes management that can be accomplished through self-management (DSM). DSM activity greatly influences patients since the patient can independently manage and apply dietary guidelines in daily life. This study aims to analyze the correlation between DSM and nutritional status in patients with diabetes mellitus. This study was conducted in three types A hospitals in Jakarta using a cross-sectional design with 260 patients with type 2 diabetes mellitus. The measurement of DSM activity was measured using the Diabetes Self-Management Questionnaire (DMSQ), measuring food intake through a questionnaire of 1x24 hours food recall and nutritional status assessed by body mass index (BMI). This study shows that 53.1 % of respondents have adequate food intake, 52. 7% of respondents have an inadequate level of diabetes self-management, and 56. 6% of respondents have abnormal nutritional status. There is a significant correlation between DSM and nutritional status (p = 0.002, OR = 2,217). Respondents with an inadequate DSM are at risk of 2,217 times experiencing abnormal nutritional status compared to respondents with an adequate DSM. It is necessary to strengthen education through diabetes self-management in dietary problems repeatedly to patients through meetings held in groups when patients come to the outpatient unit. Hence, patients can fulfill their self-care properly.